The Role of Artificial Intelligence in Revolutionizing Scientific Research and Healthcare - B.Hariharan; D.Bharathraj; I.Balaji; S.Anbazhagan; S.A.Vadivel (Asian Journal of Pharmaceutical Research and Development, 2025)
Background: Artificial Intelligence (AI) is transforming scientific research by enhancing data analysis, predictive modeling and automation across various disciplines. Its integration into fields such as healthcare, drug discovery, chemistry, physics, and environmental sciences has significantly improved efficiency and accuracy. Aim: This review aims to explore AI’s applications in scientific research, highlighting its contributions to diagnostics, personalized medicine, material discovery, and environmental modeling while addressing existing challenges and future prospects. Methods: A systematic review of AI applications in scientific research was conducted, focusing on studies utilizing machine learning (ML) and deep learning (DL) to improve predictive accuracy, optimize complex systems, and enhance decision-making. Key challenges such as algorithmic bias, data privacy, and ethical considerations were also analzed. Results: AI-driven innovations have led to breakthroughs in scientific research, including enhanced disease diagnostics, accelerated drug discovery, improved material optimization, and accurate environmental predictions. AI has also facilitated the development of personalized medicine by analyzing vast datasets with high precision. However, challenges related to data integrity, transparency, and ethical concerns remain significant barriers to widespread adoption. Conclusion: AI continues to revolutionize scientific research, yet overcoming challenges such as ethical concerns, data security, and algorithm interpretability is crucial for its full potential to be realized. Future research should focus on developing explainable AI models, fostering interdisciplinary collaboration, and establishing ethical frameworks to ensure responsible AI implementation.